Planning and implementation of Japan-Indonesia joint study of skin cancer (Faculty of Medicine Universitas Indonesia, 2000)
Masalah kanker kulit tampaknya merupakan masalah penting baik di Ind onesia maupun di J epan g. Berdasarkan minat bersama telah dikembangk an. p enelitia11 kerja sama antara Indonesia dan J epan g . telah dirancang penelitian meliputi tiga aspek , yaitu epidemiologi, klinik dan histopatologi. Kerjasama peneitian tersebut dimulai de11ga 11 p ertemuan kansultatif dan pembinaan tim yang bersifat multidisiplin baik dari pihak Ind onesia numpw1 J epang. Dalam taltap p ersiapan dilakukan identlftkasi n:a.ralah ilmiah, tujuan, makna dan ke1mtungan u/ltuk kedua be/.ah pihak, termasuk p ertukaran peng e1a/ma11, ketrampi/an da11 alih 1eknologi. Manajemen pe11 eli1ian mengikuti lima Jase, yairu p enetapan & per encanaan, perorganis asian, p engendalian dan penghe111ian , dengan penyesuaian w1tuk proyek p enelitia11 denga11 menerapka 11 Lima unsur ilmrL Peng umpulan data direncanakan denga11 penyusiman fonnulir baku untuk penelitian klinik, hisroparologi da11 kuesioner 1mtuk p enelitian epidemiologi, dilengkapi dengan pedoman untuk p ewawancara. Pengorganisasian pengim1pulan dan pemrosesan data melibatkan semua anggota tim menurut alur khusus dan jadual Gatulf. lAporan kemajuan berkala dibuat .;etelah tiap p ::rtemuan /ammitatif. Baik persamaan maupun ketidaksamaan yang ditemukan di antarnkasus kanker kulit Indonesia da11 Jepang di analisa. Hasil-lzasil preliminer dari penelitian kerjasama dipresentasika11 dan dibahas dalam Simposium Sehari dan p ertemuan ilmiah nasional da11 internasional. Makalah-makalah akan dipublikasikan dalam suatu monograf di Medical Journal of Indonesia dan majalah internasional lain. Abstract Skill cancer appeared to be an important cancer proble m in Indonesia and Japan. Based on common interest of the problem, a joint study betwee11 Japan and Indonesia 011 skin cancer has bee11 established . Three fold-study , namely epidemiological , clinical and histopathological aspects have been designed. 111e collaborative study has bee11 initiated by consultation meetings and building of multidiscplinary teams, far both Japanese and Indonesia n sides. The preparation of the joint project has bee11 initiated by the development of proposal with approval of the Dean and submitted to 1he Ministry of Education, Sport and Culture, Japan. The proposal includes the identification of scientific problems, the objectives, the significance and the merit for bath sides, including exchange of knowledge, skill and transfer of technology. The management of the research project followed five phases, namely defming & planning, organization, controlling and tennina rion, with adjustment to research project by applying five elements of science. The collection of data has been planned by developing standard fonns for clinical study, histapathological study and questionnaire for epidemiological study, accompanied by its manual for interviewers. The organization of data collection and proc essing involved all team members following special flowcha rt and Gann/ chart. Periodic progress report was made after every consultation meeting. Both simi larity and dissimilarity of the findings between Indonesian and Japanese skin cancer cases were analyzed. Preliminary results of the joint study were presented and discussed in One Day Symposium and other national and international scientific meetings. The papers are to be published in a monograph in the Medical Journal of Indonesia and other international journals . Keywords: planning, implementation, joint study, skin cancer, Indonesia and Japan.